Calcium Alginate and Salt/Phosphate as Binding Agents in Restructured Lamb - Triana Setyawardani; Sri Raharjo; purnama sudarmadji (Animal Production: Indonesian Journal of Animal Production, 2001)
A study on  restructurization of lamb meat using several binding agents were conducted. Objectives of the study were evaluate  effectivity of Ca–alginate, salt and phosphate as binding agent and their effect on physical properties of the restructured meat stored at -20⁰C for up to 12 weeks. Three binding agents were added to the restructured products, which include NaCl 0.3 %/ NTPP 0.3 %; alginate 0.5 %/Ca-lactate 0.5%; NaCl 0.3 % / NTPP 0.5 %/alginate 0.5% and no binding agent as a control. The products were evaluated at 0, 4, 8 and 12 weeks of storage. The result showed that treatment with alginate 0.5%/Ca-lactate 0.5% had the least purge loss value of 4.3±0.2%. The least cooking losses of 30.2±3.79% and the highest shear force 61.6±13.77 N. (Animal Production 3(1): 20-25 (2001)